Pengembangan Potensi Wisata Pasar Kampung Melayu Berbasis Kearifan Lokal - Rizkian, Muhammad Saleh; Sidauruk, Sri Hartati (Fakultas Ekonomi Universitas Samudra, 2025)
Pasar Kampung Melayu is a form of rural economy that has strong relevance in preserving traditional nuanced values ​​and culture with environmental characteristics that are still beautiful and sustainable which has tourism potential. This research aims to find strategies and potential in managing the Pasar Kampung Melayu by considering the ecological, economic and socio-cultural conditions of the community. Data collection was carried out through interviews and surveys on research objects and analyzed using SWOT analysis with the IFAS-EFAS approach, TOWS matrix analysis and Cartesian SWOT diagrams. The results of the research show that the Kampung Melayu Market is in the Growth Quadrant I by implementing the S-O strategy with strategic priorities of maintaining environmental beauty, the use of darham coins, and typical Malay culinary delights, maintaining supporting appearances and continuous promotional activities so that the Pasar Kampung Melayu remains a constant axis new economy.